Is Eastern European 'Double Genocide' Revisionism Reaching Museums?. Issue 3 (1st September 2016) - Katz, Dovid
Abstract : In contrast to twentieth-century Holocaust Denial, the most recent assault on the narrative of the genocide of European Jewry has emanated from a sophisticated revisionist model known as Double Genocide, codified in the 2008 Prague Declaration. Positing 'equality' of Nazi and Soviet crimes, the paradigm's corollaries sometimes include attempts to rehabilitate perpetrators and discredit survivors. Emanating from pro-Western governments and elites in Eastern Europe in countries with records of high collaboration, the movement has reached out widely to the Holocaust Studies establishment as well as Jewish institutions. It occasionally enjoys the political support of major Western countries in the context of East-West politics, or in the case of Israel, attempts to garner (eastern) European Union support. The empirical effects to date have included demonstrable impact on museums, memorials and exhibits in Eastern Europe and beyond.